Strategi Pemecahan Masalah dalam Menyelesaikan Permasalahan Kontekstual pada Materi Aljabar Mahasiswa - zahra, pingkan lailatul, Masduki, S.Si, M.Si (2017)
The purpose of this study is to describe strategy of the student in solving algebra contextual problems before and after given problem-solving based learning module. This type of research is a qualitative research, held in the first semester year of 2016/2017. Subjects were first semester students of Mathematics Education, Faculty of Teaching and Education, Universitay of Muhamadiyah Surakarta who take Basic Mathematics courses. Data collections are based on observation, test, interview, and documentation. The tests in which consist of pretest and posttest were done twice. The pre-test was done before the students were given the problem-solving based learning module. While posttest was done after the students were given the problem-solving based learning module. The method of analysis data uses three flows: reduction, data presentation, and conclusion. Data validity uses triangulation technic. The study states: (1) Strategy of students in solving contextual problems related to SPL is a trial strategy. While strategy to solve contextual problems related to geometric is a trial, trial and errordirect answer, comparison, and geometric series. Strategy to solve a contextual problem related quadratic equation and plane are by drawing and direct answer. (2) The problem-solving strategy of students before given the module did not fulfill problem-solving steps comprehensively. While the strategy of students to solve the problem after given module has fulfilled problem-solving steps.